Uji mutu fisik gel dari sari buah nanas (ananas comusus (l.) Merr) sebagai pelembab kulit - Jannatul Firdausi (Jurnal Ilmiah Farmasi Attamru (JIFA), 2021)
Pineapple contains ananasat, citric acid, saponins, tannins, flavonoids, polyphenols and enzymes bromelain, vitamin A and vitamin C which can moisturize the skin. The gel has the ability to moisturize with ingredients that contain lots of water, has a cooling effect that is good for use in hot weather and is suitable for oily skin. The purpose of this study was to determine the physical characteristics of pineapple juice gel (Ananas comusus (L) Merr) as a skin moisturizer. Pineapple juice gel was made in two formulas with different concentrations of pineapple juice, namely F1 (10%) and F2 (15%). This research is an experimental research. The working procedure consists of sample preparation, gel preparation, gel formulation formulation, gel physical quality test including organoleptic test, homogeneity test, pH test, viscosity test, dispersion test, irritation test, moisture test. The results of the F1 and F2 organoleptic tests have the same results, both formulas have a yellow color, distinctive odor, and are semi-solid. The homogeneity test of F1 and F2 has homogeneous results. F1 and F2 have a pH of 5.4-5.6. The F1 and F2 viscosity tests have a value of 4995 cPs. The dispersion test of F1 and F2 had good results, namely 5.5-5.6 cm. irritation test showed that F1 and F2 were safe to use as skin moisturizers. Moisture test on F1 and F2 showed that the gel was able to hydrate the skin with a value of 85.7%-87.6%.